2016
DOI: 10.3109/13561820.2016.1169261
|View full text |Cite
|
Sign up to set email alerts
|

Promoting interprofessional collaboration in oncology through a teamwork skills simulation programme

Abstract: Outcomes in clinical oncology can be improved when care is delivered by high-performance teams. The purpose of the initiative described in this article was to develop interprofessional team training opportunities using simulated cancer care scenarios to enhance collaborative practice skills within clinical oncology. Scenarios were developed based on internal needs assessment and review of patient safety data. Paired teams of haematology-oncology nurses and fellows completed the patient management scenarios, fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 7 publications
1
16
0
Order By: Relevance
“…Findings from our pilot study were consistent with findings from James et al (9), where the authors found that interprofessional team training is valuable to participants to gain essential interprofessional competencies.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Findings from our pilot study were consistent with findings from James et al (9), where the authors found that interprofessional team training is valuable to participants to gain essential interprofessional competencies.…”
Section: Discussionsupporting
confidence: 92%
“…Guidelines from Breast Cancer Network Australia advise, "Where appropriate, every woman should be treated in line with the principles of a multidisciplinary approach to her breast cancer treatment" (8). Although there is a growing body of evidence in relation to IPL in patient care, there are relatively few studies that have been conducted on the role of IPL in oncology (9).…”
Section: Discussionmentioning
confidence: 99%
“…In policy and the literature, the use of technology to support effective teamwork is clearly identified as a key attribute (James, Page, & Sprague, 2016;McLoughlin, Patel, O'Callaghan, & Reeves, 2018;NHS England, 2017). However, this appeared to be a source of frustration for participants.…”
Section: Discussionmentioning
confidence: 99%
“…In defining IPE, the literature suggests that it presents a flexible, sustainable approach to education. IPE is identified as being especially effective as a tool for teaching patient safety, the improvement of quality and as a means of enabling differing professional groups to understand the complexity of clinical presentations (James, Page, & Spague, 2016;Wilson, Palmer, Levett-Jones, Gilligan, & Outram, 2016). The effectiveness of IPE is rooted in its power to reflect clinical reality (Curran, Sharpe, Flynn, & Button, 2010;Machin & Jones, 2014).…”
Section: What Are the Current Challenges?mentioning
confidence: 99%